Penerapan Analisis Importance Performance Kepuasan Pasien Pada Klinik Mitra Sandona - Rizky Natassia; Hayu Yolanda Utami; Dina Amaluis (Jurnal Abdimas Saintika, 2021)
One of the development efforts in the health sector is the availability of quality health services. The clinic is a health institution that reaches out to the community directly to provide treatment to the community. In order to create excellent service, the clinic must pay attention to the services provided to patients. Patient satisfaction is very important to be considered by the clinic management. Patient satisfaction is one indicator of the success of providing health services to the community. Mitra Sandona clinic is one of the clinics located in the city of Padang. This clinic provides BPJS services to patients. Health service satisfaction is achieved if what the patient gets exceeds his expectations. To determine patient satisfaction, an analysis tool called importance performance analysis is needed. This matrix analyzes the level of expectations and experiences felt by patients. Through this matrix, the clinical management can determine which level of importance should be improved, enhanced and maintained